The Influence of Leadership Behavior and Work Discipline on The Work Effectiveness of Members in The Bandung Police Drug Research Unit - Ipung Suparna Putra; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Management Science, 2026)
The purpose of the study is to describe and analyze the influence of leadership behavior on the effectiveness of member work, the influence of work discipline on the effectiveness of member work and the influence of leadership behavior and work discipline simultaneously have a significant effect on the effectiveness of the work of members of the Bandung Police Narcotics Research Unit, the calculated tvalue for variable X1 (Leader behavior) is 7.859, while the ttable value for n = 69 is 1.995. So 7.859 > 1.995, it can be concluded that partially the variable Leadership Behavior (X1) has a significant influence on the effectiveness of member work (Y), the calculated tvalue for variable X2 (Work Spirit) is 10.669, while the ttable value for n = 69 is 1.995. So 10.669 > 1.995, it can be concluded that partially the work discipline variable (X2) has a significant effect on the effectiveness of member work (Y). The calculated fvalue is 297.332. which is greater than the table fvalue for n = 69 of 2.74 or 297.332 > 2.74 with a significance level of 0.000 because 0.000 < 0.05, it can be said that leadership behavior (X1) and work discipline (X2) jointly influence the effectiveness of member work (Y).